2015
DOI: 10.15640/jea.v3n2a11
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Of Variation Orders in Highway Projects in Jordan

Abstract: Variation orders are the most disruptive and unpleasant events of the projects because of their impacts on cost and completion date of the project. This study is about the variation orders in highway projects that are the most severe problems in the highway projects. Variation order is any modification to the contractual terms of a project by the owner or the owner's representative, it can be a work that is added to or deleted from the original scope of work of a contract, which alters the original contract am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 1 publication
0
28
0
1
Order By: Relevance
“…From the literature review, it is found that there are 18 main causes of the variation works identified by most researches ( [5], [6], [2], [7], [3], [8], [9], [10], [11], [12], [13], [14], [15], [16] and [17]). The causes of variation order are described as follows:…”
Section: The Causes Of Variation Workmentioning
confidence: 99%
“…From the literature review, it is found that there are 18 main causes of the variation works identified by most researches ( [5], [6], [2], [7], [3], [8], [9], [10], [11], [12], [13], [14], [15], [16] and [17]). The causes of variation order are described as follows:…”
Section: The Causes Of Variation Workmentioning
confidence: 99%
“…Halwatura and Ranasinghe [34] proposed that increasing communication channels and hire professional planning staff would reduce occurrence of changing orders in projects. Msallam et al [35] proposed an administration system that could reduce variation orders in Jordanian highway projects. The system applications covers all project stages (conceptual, design and construction) and collect all project rulers (owner, consultant and contractor).…”
Section: Contractual and Governmental Proceduresmentioning
confidence: 99%
“…According to variation order is one of the unfortunate conditions that disturb the flow of construction process and simultaneously delay construction project. Msallam et al (2015) conclude that variation order is a destructive and unpleasant event in a project because of their impact on cost and completion date of project. However, the authors view that variation orders are not necessarily detrimental to the success of a project but could also be beneficial in some situations.…”
Section: Introductionmentioning
confidence: 92%